The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1074/jbc.m807491200
|View full text |Cite
|
Sign up to set email alerts
|

Roles of β-Tubulin Residues Ala428 and Thr429 in Microtubule Formation in Vivo

Abstract: The C termini of ␤-tubulin isotypes are regions of high sequence variability that bind to microtubule-associated proteins and motors and undergo various post-translational modifications such as polyglutamylation and polyglycylation. Crystallographic analyses have been unsuccessful in resolving tubulin C termini. Here, we used a stepwise approach to study the role of this region in microtubule assembly. We generated a series of truncation mutants of human ␤I and ␤III tubulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 75 publications
2
17
0
Order By: Relevance
“…The C Terminus of ␣-Tubulin Is Necessary for Microtubule Incorporation-It was recently shown that the deletion of the charged C-terminal tail of ␤-tubulin impedes its incorporation in the microtubule network in vivo (42). The present results show that this is also the case with ␣-tubulin truncated of its 23 last residues (GFP-Tub⌬23C).…”
Section: Discussionsupporting
confidence: 67%
“…The C Terminus of ␣-Tubulin Is Necessary for Microtubule Incorporation-It was recently shown that the deletion of the charged C-terminal tail of ␤-tubulin impedes its incorporation in the microtubule network in vivo (42). The present results show that this is also the case with ␣-tubulin truncated of its 23 last residues (GFP-Tub⌬23C).…”
Section: Discussionsupporting
confidence: 67%
“…Bands were transferred to nitrocellulose membranes and treated with isotype-specific monoclonal antibodies followed by horseradish peroxidase as described by Joe et al (2009). Bands were quantitated by image analysis using the Odyssey software (LI-COR Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Unlike the bII-and bIV-tubulin isotypes bIII-tubulin is phosphorylated at a serine in the C-terminus (Khan and Ludueña, 1996;Ludueña and Banerjee, 2008b). Also, unlike in other b-tubulin isotypes, in the bIII isotype, the presence of threonine residue Thr(429) strongly favors microtubule assembly (Joe et al, 2009). And finally, notwithstanding its restricted and highly selective (predominantly neuronal) cell type distribution in normal organs and tissues, the bIII isotype is widely, albeit differentially, expressed in a broad range of human tumors of neuronal and non-neuronal origin (Katsetos et al, 2003a,b).…”
Section: Microtubules and Tubulinsmentioning
confidence: 97%